Crossing the Mediterranean: Media Coverage of Europe’s 21st century Refugee Crisis - Abhijit Sen (Athens Journal of Mass Media and Communications)
The history of mankind is replete with movements of human beings across our large planet. People moved or were forced to move because they could no longer live at one place in peace and stability. Wars and famines were common reasons to uproot the tents and move on to greener pastures but there were other reasons as they are still today. One of the major causes of leaving one’s homeland is inter-tribal or inter-ethnic rivalry and the other is religious persecution. As we see in Middle-East or West Asia as commonly designated now, these causes are still alive and festering like unhealed wounds making people leave the safety of their homes and family for a more hospitable environment. Into this mixture of geo-politics and ideologies promoted by the super-powers, a complex situation has become more complicated leading countries to take sides and fight proxy wars. The ‘migrants’ and ‘refugees’ streamed in via various routes especially by crossing the Mediterranean. Whether these asylum seekers could be classified as migrants or refugees is contentious. One study examines how the very concepts of ‘migrant’ and ‘refugee’ are used in different contexts, and introduces questions about mobility, citizenship and the nation state. The media and the press continued to refer to the people leaving conflict zones as migrants looking for a better economic opportunity. Responsible journalists depicted refugees and their desperate situation in a balanced and sympathetic context but a majority of news media channels took the sensationalist and ideologically biased road, playing on people’s anti-immigration sentiment, anxiety and fears.